REPRODUCTION OF ENTOMOPATHOGENIC NEMATODES Steinernema carpocapsae AND Heterorhabditis bacteriophora ON THE GERMAN COCKROACH Blatilla germanica AT DIFFERENT TEMPERATURES. - Baker, N.; Ali, Hayder; Gowen, S. (Iraqi Journal of Science, 2024)
Adult and nymph stages of German cockroaches Blatilla germanica were infested with two entomopathogenic nematodes, Steinernema carpocapsae and Heterorhabditis bacteriophora in vitro at 15, 20, 25o C. Results showed that S. carpocapsae was more virulent than H. bacteriophora at all temperatures over the exposure times of 24, 48 and 72 h. Infection of nymphs by S. carpocapsae at 20o C caused 100% mortality after 72h and 100% mortality of adults at 25 o C after 72h. Reproduction of S. carpocapsae significantly increased at 25o C after 72 h compared to H. bacteriophora.